KONSEP MANAJEMEN PEMBIAYAAN PENDIDIKAN PADA LEMBAGA PENDIDIKAN ISLAM - Ulfa Dj. Nurkamiden; Herson Anwar (LP2M IAIN Sultan Amai Gorontalo, 2023)
This article aims to see how the concept of education financing management is in Islamic Education Institutions, so that it can find new formulations in financing management. The research method used in this research is library. Namely research whose data was found through literature review and other references related to this research. The results of this study found that financial management in Islamic educational institutions needs to be carried out as well as possible so that all educational operational activities can be carried out smoothly and properly. In this regard, leaders of Islamic educational institutions need to have knowledge regarding the management of funding for Islamic educational institutions, so that they can run the organization well.